The young gold diggers - Earnshaw, Beverley; Gill, Samuel Thomas, 1818-1880; Kogarah Historical Society ([Kogarah, New South Wales] : [Kogarah Historical Society], 2014)
"In 1835 two boys aged 9 and 11 walked with their father from Sydney to the Bathurst gold diggings, a distance of about 200 kilometres. There they joined the merry community of a gold diggers prospectors on the Ophir and Turon gold fields. They observed first hand the miners at work, panning, wheeling, cradling, shafting and tunnelling in their search for gold. The boys acquired a scraggy dog and this led to a brief encounter with the bushrangers." --Back cover.
For primary school age.
Keywords: Boys -- New South Wales -- Bathurst Region -- Juvenile fiction; Gold miners -- New South Wales -- Bathurst Region -- Juvenile fiction; Gold mines and mining -- New South Wales -- Bathurst Region -- History -- Juvenile fiction; Gold dredging -- New South Wales -- Bathurst Region -- History -- Juvenile fiction; Gold panning -- New South Wales -- Bathurst Region -- History -- Juvenile fiction; Bathurst (N.S.W.) -- Social life and customs -- 19th century -- Juvenile fiction; Australian